First Report of CTNS Mutations in a Chinese Family with Infantile Cystinosis. (17th March 2015) - Yang, Yong-jia; Hu, Yuan; Zhao, Rui; He, Xinyu; Zhao, Liu; Tu, Ming; Zhou, Lijun; Guo, Jihong; Wu, Linqian; Zhao, Tantai; Zhu, Yi-min
Abstract : Infantile cystinosis (IC) is a rare autosomal recessive disorder characterized by a defect in the lysosomal-membrane transport protein, cystinosin. It serves as a prototype for lysosomal transport disorders. To date, several CTNS mutations have been identified as the cause of the prototypic disease across different ethnic populations worldwide. However, in Asia, the CTNS mutation is very rarely reported. For the Chinese population, no literature on CTNS mutation screening for IC is available to date. In this paper, by using the whole exome sequencing and Sanger sequencing, we identified two novel CTNS splicing deletions in a Chinese IC family, one at the donor site of exon 6 of CTNS (IVS6+1, del G) and the other at the acceptor site of exon 8 (IVS8-1, del GT). These data give information for the genetic counseling of the IC that occurred in Chinese population.